THE FORMAL-ANALYTICAL DESCRIPTION OF WOOD FOR THE PURPOSES OF THE CLASSIFICATION OF WOOD SPECIES. PART 2. WOOD FORMULAS (Innovation in Woodworking Industry and Engineering design, 2026)
The structure of wood can be examined at several qualitatively different levels of consideration (macro, meso, micro and nano). Each of these levels can be considered as a separate, single and relatively independent subsystem in the wood structure. They are determined by the characteristics of the species, the ecology of the global, regional and local habitats. Each of these levels requires a separate, more precise and comprehensive classification. If the quantities and distribution of the main tissues are known, the tree species can be grouped in groups of construction and conclusions can be made about its physical and mechanical properties.This work examines the possibility for a more in-depth formal-analytical description of the individual tree species and a theoretical representation of wood structure that more adequately reflects its characteristic features.